How Do Bank Capital and Capital Adequacy Regulation Affect the Monetary Transmission Mechanism? - Misa Tanaka (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper analyzes the effect of bank capital adequacy regulation on the monetary transmission mechanism. Using a general equilibrium framework and a representative bank, the model demonstrates that the monetary transmission mechanism is weakened if banks are poorly capitalized, or if the capital adequacy requirement is stringent. The paper also assesses the impact of the New Basel Accord (Basel II), and argues that a rise in credit risk may lead to a sharper loan contraction under this new regime. Moreover, it predicts that Basel II may reduce the effectiveness of monetary policy as a tool for stimulating output during recessions.
Keywords: 330